Understanding the dynamic interinfluences of implementation processes: An illustration by multiple case studies - Goulet, Mélissa; Archambault, Isabelle; Janosz, Michel; Bélanger, Jean; Christenson, Sandra L. (Evaluation and program planning, 2020)
•Implementation processes shed new light on program outcomes.•Implementation processes can act as either facilitators or barriers to implementation.•Implementation processes and the dynamics intervening between them help portray implementation experiences in four sites. Many dropout prevention programs have been developed and validated in the past decades. Yet, little is known about the contextual factors influencing the implementation of these programs. Implementation processes, such as school principal leadership and governmental funding, have been identified for their influence on program implementation, but the mutual or dynamic influence of these processes is yet to be understood. This study examines the processes involved in the implementation of Check & Connect (C&C), a well-established targeted dropout prevention program validated in several countries that aims at promoting the development of a significant relationship between at-risk students and a mentor as a way to prevent school dropout. Semi-structured interviews were conducted with 12 mentors and coordinators directly involved in C&C implementation. Analyses were conducted in two subsequent steps: thematic analyses first helped identify implementation processes described by respondents, and then synthetic case studies allowed us to build the implementation stories of distinct sites. This last step was conducted using the Planned Change Framework. This framework helped us to understand the complex dynamics of implementation processes in each site, which were associated with previously identified program outcomes, beyond implementation fidelity. Implications for future implementations of evidence-based programs in the school setting are discussed.